Papilla surgery. Introduction: Round Table Papilla surgery - Delgado, Bolivar; Berri, Ricardo; Cendán Alfonzo, Juan; De Los Santos, Julio; Praderi, Raúl; Sojo, Enrique; Sugasti, Juan A. (Cirugía del Uruguay, 1975)
???